2016
DOI: 10.1371/journal.pone.0147329
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of End-Stage Renal Disease in the Diabetic (Compared to the Non-Diabetic) Population: A Systematic Review

Abstract: End-stage renal disease (ESRD) in diabetes is a life threatening complication resulting in a poor prognosis for patients as well as high medical costs. The aims of this systematic review were (1) to evaluate the incidence of ESRD due to all causes and due to diabetic nephropathy in the diabetic population and differences between incidences of ESRD with respect to sex, ethnicity, age and regions, (2) to compare incidence rates in the diabetic and non-diabetic population, and (3) to investigate time trends. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
111
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 160 publications
(119 citation statements)
references
References 59 publications
(155 reference statements)
6
111
1
1
Order By: Relevance
“…An increase in incidence rate of end stage renal disease (ESRD) due to diabetic nephropathy (DN) was expected correspondingly severe individual and social consequences. [8] Diabetic retinopathy (DR) is the principal cause of blindness in diabetes patients and its cases are mounting gradually. [9] Long term complications of diabetes include peripheral neuropathy (PN) and peripheral vascular disease (PVD).…”
Section: Introductionmentioning
confidence: 99%
“…An increase in incidence rate of end stage renal disease (ESRD) due to diabetic nephropathy (DN) was expected correspondingly severe individual and social consequences. [8] Diabetic retinopathy (DR) is the principal cause of blindness in diabetes patients and its cases are mounting gradually. [9] Long term complications of diabetes include peripheral neuropathy (PN) and peripheral vascular disease (PVD).…”
Section: Introductionmentioning
confidence: 99%
“…Diabetic nephropathy is a very concerning microvascular complication of diabetes mellitus, whose global incidence is on the rise, rapidly12. It has been established that diabetic nephropathy eventually progresses into end-stage renal disease and is the leading cause for renal replacement therapy in developed countries3.…”
mentioning
confidence: 99%
“…Recently, it has been shown that among older patients with type 2 diabetes and endstage renal disease (ESRD), mortality rates were higher among women than men. 21 Finding also showed that education (level of schooling) was not a significant predictor among urban women; while in other countries education is a highly significant predictors of quality of life among women with type 2 diabetes as compared to men. 19 This means that the people's knowledge about type 2 diabetes needs to be enhanced through public health education.…”
Section: Discussionmentioning
confidence: 87%